Depicting Precise Temperature and Duration of Vernalization and Inhibiting Early Bolting and Flowering of Angelica sinensis by Freezing Storage - Liu, Xiaoxia; Luo, Mimi; Li, Mengfei; Wei, Jianhe (Frontiers in Plant Science, 2022)
Angelica sinensis is a perennial rhizomatous herb that is widely used for the treatment of cardio-cerebrovascular diseases, which largely rely on metabolites, such as alkylphthalides, polysaccharides, and ferulic acid. This plant must experience low-temperature vernalization and long-day conditions for the occurrence of early bolting and flowering (EBF) that reduces yield and quality of fleshy root. In current commercial planting, the EBF of more than 40% is mainly attributed to the completion of vernalization of seedlings during overwinter storage. While effects of storage temperatures [vernalization temperature (0–10°C) and freezing temperature (−2 to −12°C)] and seedling sizes on the EBF have been observed in previous studies, the precise vernalization temperature and duration for different size seedlings, the effective freezing storage to avoid vernalization of seedlings, and physiological characteristics have not been systematically investigated. Here, the EBF rate, the anatomical structure of shoot apical meristem (SAM), and physiological characteristics of different size seedlings at different storage temperatures (0, 3, 5, −3, and −5°C) and durations (14–125 d) are reported. The vernalization duration of seedlings was predicated from 57 to 85 d with temperatures ranging from 0 to 5°C based on the linearization regression analysis via Matrix Laboratory software. The EBF can be effectively inhibited by freezing storage. The anatomical structure of SAM, levels of primary metabolites (soluble sugar, starch, amino acid, and protein), and endogenous hormones (GA3, IAA, and ABA), exhibited a dynamical change in the seedlings at different storage temperatures. These findings will provide useful information for predicting the vernalization of seedlings and inhibiting the EBF in large-scale commercial cultivation.